In Depth: Unveiling hate speech in the digital world - Mila Ibrahimova (The UNESCO Courier, 2023)
Hate speech is nothing new, but the phenomenon is spreading at an unprecedented rate and scale in the age of social media. Both online and offline, it targets a person or a group on the basis of who they are. Hate speech not only causes harm at the personal level; it also undermines social cohesion. In response to this alarming trend, the United Nations proclaimed, in 2022, 18 June as the International Day for Countering Hate Speech. UNESCO, actively engaged in the fight against online hate speech through education, emphasizes the urgent need for common principles worldwide to improve the reliability of information while protecting human rights.